Growth differentiation factor 15 is increased in stable MS. Issue 2 (March 2020) - Amstad, Andrea; Coray, Mali; Frick, Corina; Barro, Christian; Oechtering, Johanna; Amann, Michael; Wischhusen, Jörg; Kappos, Ludwig; Naegelin, Yvonne; Kuhle, Jens; Mehling, Matthias
Abstract : Objective: To assess whether serum concentrations of the anti-inflammatory cytokine growth differentiation factor 15 (GDF-15) differ in patients with highly active multiple sclerosis (MS) vs patients with stable MS and healthy controls (HCs). Methods: GDF-15 concentrations were measured by ELISA in serum and CSF in a cross-sectional cohort of patients with MS, patients with other inflammatory neurologic diseases (OIND), patients with noninflammatory neurologic diseases (NIND), and healthy controls (HC). Serum GDF-15 concentrations were measured in a longitudinally sampled cohort of clinically and radiologically well-characterized patients with MS and corresponding controls. Results: Cross-sectionally measured median serum GDF-15 concentrations were significantly higher in patients with OIND (n = 42) (600 pg/mL, interquartile range [IQR] = 320–907 pg/mL) compared with HCs (n = 29) (325 pg/mL, IQR = 275–419 pg/mL; p = 0.0007), patients with NIND (n = 46) (304 pg/mL, IQR = 245–493 pg/mL; p = 0.0002), or relapsing MS (n = 42) (356 pg/mL, IQR = 246–460 pg/mL; p = 0.0002). CSF and serum concentrations of GDF-15 were correlated (r = 0.41, 95% CI = 0.25–0.56, p < 0.0001). In a longitudinally sampled cohort of patients with MS (n = 48), deeply phenotyped with quantitative clinical and MRI assessments, mean GDF-15 concentrations were significantly higher in patients with a stable disease course (405 pg/mL, SD = 202) than in patients with intermittent MRI activity (333 pg/mL, SD = 116; p = 0.02). Conclusions: Serum GDF-15 concentrations are increased in patients with MS with a stable disease course. These data suggest that GDF-15 may serve as a biomarker for disease stability in MS.